CREATING A POSITIVE WORKING ENVIRONMENT FOR TEACHERS - Geske, Andrejs; Zizlāne, Liene (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the research paper is to study a positive working environment importance for teachers work satisfaction and the role of principal in improving working conditions. Whereas teacher profession is subject to different changes and reforms it makes the whole profession and teacher well-being an important subject to discuss.The research paper includes analysis of the theoretical material about physical environment as well as psychological (also called microclimate). Empirical part is based on teacher’s survey – 97 teachers from different schools in Riga were involved. The statements of survey have partially adopted from Teaching and Learning International Study TALIS 2013. The main research task is to study how work environment and the impact of principal correlate with teacher work satisfaction.During research scales of teacher work satisfaction, work environment and impact of principal were created. The results of linear regression show that both the work environment and direct impact of principal is important factor which influences as well educational work as work satisfaction. The situation is various in different schools in Riga, so it verifies, that the problematics of positive working environment exists.